Oil Price and Capital Formation Nexus in GCC Countries: Asymmetry Analyses - Alkhateeb, Tarek Tawfik Yousef; Mahmood, Haider (International Journal of Energy Economics and Policy, 2020)
Oil Price (OP) may support the oil dependent economies in term of macroeconomic performance. We investigate the asymmetrical effect of OP on capital formation of Gulf Cooperation Council (GCC) countries. We found long and short relationship in all GCC models. Increasing OP has positive effect on capital formation of all GCC countries except Oman and Qatar in long run. Decreasing OP has positive effect on capital formation in UAE, Saudi Arabia and Bahrain. Increasing OP has positive effect on capital formation of Bahrain and UAE and carries negative impact in Kuwait and Qatar in short run. Decreasing OP positively affects the capital formation of Bahrain and Saudi Arabia and has negative effect in Kuwait, Oman and UAE. Moreover, asymmetrical effect of OP on capital formation is verified in GCC countries except UAE in long run and in all GCC countries except Bahrain and Kuwait in short run. Keywords: Oil price, Capital formation, Asymmetry JEL Classifications: P28, E22, D82 DOI: https://doi.org/10.32479/ijeep.10013